Non‐suicidal self‐injury and its co‐occurrence with suicidal behavior: An epidemiological‐study among adolescents and young adults. (22nd October 2020) - Voss, C.; Hoyer, J.; Venz, J.; Pieper, L.; Beesdo‐Baum, K.
Abstract : Objective: Non‐suicidal self‐injury (NSSI) comprising thoughts and behaviors is common and often co‐occurring with suicidal behavior like ideation, plan, and attempt. As limited data are available for adolescents and young adults, this study aims to present prevalence estimates for lifetime NSSI, its co‐occurrence with suicidal behavior, conditional probabilities and their association with socio‐demographic characteristics, severity characteristics of suicidal behavior, and health service utilization. Method: The epidemiological Behavior and Mind Health (BeMIND) study assessed in 2015/16 a random‐community sample of N = 1180 aged 14–21 years from Dresden, Germany, regarding lifetime NSSI via self‐administered questionnaire and suicidal behaviors via standardized interview. Results: Any lifetime NSSI was reported by 19.3% (thoughts: 18.0%, behaviors: 13.6%) of the sample with higher prevalence in females ( OR = 2.7, 95% CI 1.9–3.8, P < 0.001). Lifetime prevalence of co‐occurring NSSI and suicidal behavior was 7.7%. Females had a 3.3‐ to 8.8‐fold odds of co‐occurrence than males. Among those with any NSSI, 39.6% endorsed suicidal behavior, and 66.3% of those with any suicidal behavior reported NSSI. 42.3% of those with any NSSI reported to have used mental healthcare services at any time during their life with higher rates in those with co‐occurring suicidal behavior (62.3%). Conclusion: Non‐suicidal self‐injury and co‐occurring suicidal behavior is common in adolescents and young adults—especially females. The limited utilization of mental healthcare services underpins the need for improving recognition of NSSI and suicidal behavior as well as the accessibility of mental healthcare services during adolescence and emerging adulthood.